New Trends in Nuclear Science - Sayed Awwad, Nasser; AlFaify, Salem A. (IntechOpen, 2018)
This book will hopefully shed light on some of the advances taking place within nuclear science research in recent times. It describes the interesting results of some modern nuclear science research carried out by bright scientists and researchers in different parts of the world. The book is divided into five chapters. The first one is an introductory chapter to explain the nature and purpose of the book and the logic and significance of its contents. The second chapter is a concise introduction to the core subject of nuclear science, which is the nuclear reactions. This chapter also touches on the fundamental and basic physics underlining major nuclear reactions. Chapter three addresses some recent advances related to the famous nuclear detector material namely CdTe. The authors suggest that the modern detector based on CdTe materials can be developed as a multi-element detection platform that allows for the direct conversion of information generated by passing X/y-radiations through an examined object into an array of digital electrical signals without using an intermediate visible image on a fluorescent screen. In chapter four, a new study on the effect of unintended and accidental nuclear impact on the environment is discussed. In the last chapter, Thomas W. Grimshaw; from The University of Texas at Austin, USA; has composed an interesting study on the so-called cold nuclear fusion or the more widely known low energy nuclear reaction (LENR). He, among others, argues that nuclear cold fusion, if realized and understood, could be a significant source of cheap and clean energy. This book will hopefully encourage readers, researchers, and scientists to look further into the frontier topics of modern nuclear science and make the needed efforts to develop its cause and uses.